Study of inclusive B- and B̄0 decays to flavor-tagged D, Ds, and Λc+ - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2007)
We report on a study of inclusive B- and B̄0 meson decays to D0X, D̄0X, D+X, D-X, Ds+X, Ds-X, Λc+X, Λ̄c-X, based on a sample of 231×106 BB̄ events recorded with the BABAR detector at the Υ(4S) resonance. Events are selected by completely reconstructing one B and searching for a reconstructed charm particle in the rest of the event. From the measured branching fractions of these decays, we infer the number of charm and anticharm particles per B̄ decay, separately for charged and neutral parents. We derive the total charm yield per B- decay, nc-=1.208±0. 023±0.040-0.029+0.035, and per B̄0 decay, nc0=1.203±0. 030±0.034-0.035+0.044 where the first uncertainty is statistical, the second is systematic, and the third reflects the charm branching-fraction uncertainties. We also present the charm momentum distributions measured in the B̄ rest frame. © 2007 The American Physical Society.